Identification and Assessment of Food Safety Risk in Betutu Chicken Products Retort Pouches Packaged - Indriyani, Siti Patimah; Setyaningsih, Dwi; Hardjomidjojo, Hartrisari (Universitas Djuanda, 2026)
Retort pouch of betutu chicken products have the potential to be an export product, oriented towards expanding Indonesian culture in the form of traditional food. Commercial sterile food products are included in the high-risk category, so food safety risk control needs to be carried out in accordance with the BPOM Regulation Number 10 of 2023 concerning the Implementation of the Risk Management Program (RMP). This study aims to analyze the food safety risks of the retort pouch Betutu Chicken production of Mustafafood Indonesia MSMEs, and determine critical control points. The approach employed in this study was descriptive qualitative, utilizing the hazard analysis method and decision tree. The processes identified as having significant hazards included raw material receiving, sterilization, cooling shock and product quarantine. The critical control points in the production betutu chicken retort pouch were raw material receiving with chemical hazards (heavy metals), as well as the sterilization process, associated with biological hazards (C.botulinum). The control measures implemented for the receipt of raw materials and cooking process comprised the use of metal detectors. For the sterilization process, control was exercised through process monitoring focusing on critical limits and validation of heat adequacy values.